Ratio of Cesarean Sections to Total Procedures as a Marker of District Hospital Trauma Capacity - Petroze, Robin T. (2012)
BACKGROUND: There are few established metrics to define surgical capacity in resource-limited settings. Previous work hypothesizes that the relative frequency of cesarean sections (CS) at a hospital, expressed as a proportion of total operative procedures (%CS), may serve as a proxy measure of surgical capacity. We attempted to evaluate this hypothesis as it specifically relates to hospital capacity for emergency interventions for injury. METHODS: We conducted a WHO survey of emergency surgical capacity at 40 Rwandan district hospitals in November 2010 and extracted annual operative volume for 2010 from the Ministry of Health centralized statistical system. We dichotomized the 40 hospitals into low and high %CS groups below and above the median proportion of CS performed. We compared low and high %CS groups across self-reported capabilities related to facility characteristics, trauma supplies, procedural capacity, and surgical training using bivariate χ(2) statistics with significance indicated at p ≤ 0.05. We evaluated herniorrhaphy proportion of total procedures (%Hernia) as a representative general surgery procedure in the same manner. RESULTS: High %CS hospitals were less likely to report capability related to blood banking (p = 0.05), amputation (p = 0.04), closed fracture repair (p = 0.04), inhalational anesthesia (p = 0.05), and chest tube insertion (p = 0.05). Availability of reliable electricity was the only measure that showed statistical significance with the %Hernia measure (p = 0.02). CONCLUSIONS: Cesarean section proportion shows some utility as a marker for district hospital injury-care capacity in resource-limited settings.